Student’s Mathematical Understanding Ability on Solving Mathematical Problems in Terms of Adversity Quotient - Fhuzi Kartin Astuti; Usman Aripin ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2022)
Education is one of the learning processes to improve a person's skills and behavior. Mathematical understanding is the ability to understand concepts, the ability to distinguish concepts, and the ability to calculate complex situations or problems. Adversity quotient is the response of a person or individual when faced with problems or difficulties in his life. The main problem in one of the schools in Sumedang is the students' thinking about mathematics lessons, where this lesson is less preferred than other lessons. The method used by this study is descriptive quantitative. This research was carried out in the even semester of 2021/2022, in one of the regional schools in Sumedang, class VII totaling 15 students. The data generated from this research is in the form of an instrument, which consists of indicators of students’ mathematical understanding and there are 3 questions on indicators of mathematical understanding. The methods of data collection in this study are as follows: 1) test descriptions of questions or instruments to determine students’ understanding abilities, 2) direct interviews with students. Research results from student answers according to students’ understanding abilities in terms of AQ, as follows:  1) The results of student responses in terms of Adversity Quotient as many as 3 Climber type students (high) the average percentage of students’ understanding ability is 80%, 2) The results of students responses in terms od Adversity Quotient as many as 9 Climber students (enough) the average percentage of students’ understanding ability is 5,77%, 3) The results of students responses in terms of the Adversity Quotient as many as 3 students Cumper type (medium)the average percentage of students’ understanding ability is 15,1%.